Embodied earth kinship: interoceptive awareness and relational attachment personal factors predict nature connectedness in a structural model of nature connection - Branham, Lindsay (Frontiers in Psychology, 2024)
Previous research has found that nature connectedness, an experiential close connection to nature with cognitive, affective and physical benefits, profoundly impacts individual wellbeing and subsequently increases pro-environmental behaviours. However, little is known about the personal and contextual factors that predict nature connectedness. Testing theory derived from a qualitative interpretative phenomenological analysis study, this research addresses the lacuna in the literature. A structural equation model analysis finds that interoceptive awareness significantly predicts nature connection, that secure attachment to nature significantly explains this relationship, and that these inter-related constructs predict both pro-environmental behaviour and wellbeing. This revised model of nature connection indicates important antecedents for the human-nature bond, illuminating in particular that the interpersonal relational processes foundational for close bonding with humans also occur in bonding with nature. Structural equation modelling indicates that emotional awareness is the dimension of interoceptive awareness that most significantly predicts nature connection, suggesting that the more aware a person is of the connection between inner bodily sensations and emotions, the more likely they can bond with nature. Given that interoceptive awareness indicates a coherent relationship with the self, including effective communication between body, mind and feelings, this process is therefore implicated in the capacity for humans to bond with nature. In sum, this present research points to the efficacy of an embodied, secure attachment with nature to help close both the human-nature disconnection chasm, and the environmental value-action gap. Theoretical and methodological implications for research and policy are discussed.